The stars are fire [large type] - Shreve, Anita (Random House Large Print, 2017)
October 1947. After a summer long drought, fires break out all along the Maine coast and are soon racing out of control. Five months pregnant, Grace Holland is left alone to protect her two toddlers when her husband, Gene, joins the volunteer firefighters. Along with her best friend, Rosie, and Rosie's two young children, Grace watches helplessly as their houses burn to the ground, the flames finally forcing them all into the ocean as a last resort. Awaiting news of their husbands' fate, facing an uncertain future in a town that no longer exists, Grace discovers joys and triumphs she could never have expected her narrow life with Gene could contain.